Asymptotic expansions for renewal processes - Aleškevičienė, A. (Lithuanian Mathematical Journal, 1969)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:А. Алешкявичене. Асимптотические разложения для процессов восстановленияA. Aleškevičienė. Atstatymo procesų asimptotiniai išdėstymai